2006
DOI: 10.1128/aac.50.5.1773-1779.2006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Multiple-Dose Pharmacokinetics of Human Monoclonal Antibodies (MAbs) against Human Immunodeficiency Virus Type 1 Envelope gp120 (MAb 2G12) and gp41 (MAbs 4E10 and 2F5)

Abstract: While certain antibodies directed against the human immunodeficiency virus (HIV) envelope have the potential to suppress virus replication in vitro, the impact of neutralizing antibodies in vivo remains unclear. In a recent proof-of-concept study, the broadly neutralizing monoclonal antibodies 2G12, 4E10, and 2F5 exhibited inhibitory activities in vivo, as exemplified by a delay of the viral rebound following the interruption of antiretroviral therapy. Unexpectedly, the antiviral effect seen was most prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 48 publications
8
56
0
Order By: Relevance
“…Phase 1 clinical trial has confirmed that 2F5 is safe and well tolerated by injection (Armbruster et al, 2002). Consistent data have been obtained from a phase 2 long-term multiple-dose pharmacokinetics study conducted in HIV-1 infected patients (Joos et al, 2006). The antibody-dependent cell cytotoxicity (ADCC) induced by 2F5 contributes to the elimination of HIV-1 infected cells (Tudor and Bomsel, 2011).…”
Section: Passive Immunization Using Neutralizing Antibodiessupporting
confidence: 51%
See 2 more Smart Citations
“…Phase 1 clinical trial has confirmed that 2F5 is safe and well tolerated by injection (Armbruster et al, 2002). Consistent data have been obtained from a phase 2 long-term multiple-dose pharmacokinetics study conducted in HIV-1 infected patients (Joos et al, 2006). The antibody-dependent cell cytotoxicity (ADCC) induced by 2F5 contributes to the elimination of HIV-1 infected cells (Tudor and Bomsel, 2011).…”
Section: Passive Immunization Using Neutralizing Antibodiessupporting
confidence: 51%
“…To note, substitutions in the MPER contributed to the resistance to 4E10 (Gray et al, 2008;Nakamura et al, 2010). The safety and tolerability of 4E10 for clinical use have also been confirmed by a phase 2 clinical study (Joos et al, 2006). In rhesus macaques, passive immunization of 4E10 and 2F5 provides protection against intrarectal challenge with SHIV (Hessell et al, 2010) and delays the viral rebound in HIV-1 infected patients .…”
Section: Passive Immunization Using Neutralizing Antibodiesmentioning
confidence: 77%
See 1 more Smart Citation
“…2F5 and 4E10 mAb reactivity has been administered to a number of HIV-1-infected patients with no thrombotic event noted (51), although when these mAbs are administered, patient sera become positive in anti-cardiolipin and lupus anti-coagulant Ab assays (52). However, the MPER mAbs, 2F5 and 4E10, were not the contributing factor in the minimal effect observed on viral load (51,53). Thus, while these Abs may not be pathogenic and not cause thrombotic disease when administered to HIV ϩ patients, the relevance of our study resides in the notion that 2F5 and 4E10 have polyreactivity for various self Ags, and have structural and reactivity pattern similarities to known autoantibodies.…”
Section: Discussionmentioning
confidence: 67%
“…The 4E10 Ab has also a polyspecificity for autoantigens as histone or DNA in systemic lupus erythematosus. Several in vivo pharmacokinetic studies and phase I/II clinical trials phases I and II with combination of 4E10, 2F5 and 2G12 showed that these three Abs are able to maintain undetectable viral load in patients where the infection has been suppressed by antiviral therapy (Joos et al, 2006). These studies also showed that 4E10 administration is not highly immunogenic with rare IgM against 4E10 but no IgG.…”
Section: Mper (Membrane-proximal External Region)mentioning
confidence: 57%